2022
DOI: 10.1097/md.0000000000031185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotics on functional constipation in adults: A randomized, double-blind controlled trial

Abstract: Background: Two formulations were developed in the form of an oral sachet containing probiotics, and their efficacy and safety were evaluated in adults with functional constipation. Methods: One formulation with Lactobacillus acidophilus, Bifidobacterium bifidum and Lactobacillus rhamnosus (3 billion Colony Forming Units -CFU); and another with Lactobacillus acidophilus, Bifidobacterium bifidum, Lactobacillus rhamnosus, Lactobacillus paracasei, Bifidobacterium longum, Bifidobacterium lactis, Lactobacillus case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Mitelmo et al's RCT demonstrated that probiotic blends containing three or eight strains effectively improved functional constipation symptoms, increasing evacuation frequency and stool quality from the first week of treatment [20]. They highlighted the cost-effectiveness of prebiotics over probiotics, though probiotics' diverse health benefits were evident, including gut health maintenance, pathogenic bacteria inhibition, and immune system enhancement [20]. Ojetti et al's study also confirmed the efficacy of L. reuteri in increasing bowel movement frequency in adults with chronic functional constipation [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitelmo et al's RCT demonstrated that probiotic blends containing three or eight strains effectively improved functional constipation symptoms, increasing evacuation frequency and stool quality from the first week of treatment [20]. They highlighted the cost-effectiveness of prebiotics over probiotics, though probiotics' diverse health benefits were evident, including gut health maintenance, pathogenic bacteria inhibition, and immune system enhancement [20]. Ojetti et al's study also confirmed the efficacy of L. reuteri in increasing bowel movement frequency in adults with chronic functional constipation [23].…”
Section: Discussionmentioning
confidence: 99%
“…References: [16][17][18][19][20] The results of five studies showed an odd ratio of 2.01 in the efficacy of probiotics vs. placebo groups. The odds ratio was 2.01 (fixed effect, 95%).…”
Section: Placebo Groupsmentioning
confidence: 99%
“…A Brazilian RCT by Mitelmão et al compared the efficacy of a probiotic mixture containing three strains of Lactobacillus and Bifidobacterium , another mixture containing eight strains, and conventional fiber therapy in adults with constipation. All interventions were safe and effective in improving symptoms of constipation; however, no significant difference was seen between the groups [ 92 ].…”
Section: Role Of Prebiotics and Probiotics For Various Gastrointestin...mentioning
confidence: 99%
“…Прием пробиотиков может уменьшить функциональные запоры и повысить как количество еженедельных дефекаций, так и качество стула [49]. Пробиотические продукты вызывают положительные изменения в кишечной микробиоте, увеличивая частоту дефекаций и улучшая качество стула [50].…”
Section: результаты и их обсуждениеunclassified